Perspectiva educacional colectiva: una experiencia significativa - Castiblanco Regalado, Yamid Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article summarizes the process of the formation of the first research center of the Bachelor in Basic Education of the Chiquinquirá section, ex- plaining the process of emergence, the methodology of work that is used there, and the social construction that takes place in these media. Processes, foundations many times invisible to common ideas, then there is an osten- tation of what is behind the investigation in a hotbed.